Reliable oxygen transfer in MgAl2O4 spinel through the reversible formation of oxygen vacancies by Cu2+/Fe3+ anchoring. (1st June 2018) - Do, Jeong Yeon; Son, Namgyu; Park, No-Kuk; Kwak, Byeong Sub; Baek, Jeom-In; Ryu, Ho-Jung; Kang, Misook
Graphical abstract: Reliable oxygen transfer in MgAl2 O4 spinel through the reversible formation of oxygen vacancies by Cu 2+ /Fe 3+ anchoring. Highlights: Cux Mg1-x Fey Al2-y O4 spinel structured oxygen carriers were successfully prepared. Reversible oxygen vacancies were observed in a Cux Mg1-x Fey Al2-y O4 spinel structure. CH4 and CO gases were much adsorbed on the surface of Cu0.75 Mg0.25 Fe1.5 Al0.5 O4 spinel particle. The greatest oxygen transfer in Cu0.75 Mg0.25 Fe1.5 Al0.5 O4 particle was obtained. Abstract: This study focused on Cux Mg1-x Fey Al2-y O4 oxygen carriers for application in the chemical looping combustion of methane. Cux Mg1-x Fey Al2-y O4 was fabricated by simultaneously substituting Mg 2+ and Al 3+ with Cu 2+ and Fe 3+ in the spinel structure of MgAl2 O4 . As a result, a great synergistic effect was observed: Cu0.75 Mg0.25 Fe1.5 Al0.5 O4 exhibited 7.85% oxygen transfer capacity in the CH4 -CO2 /air redox system. Methane and carbon monoxide were significantly adsorbed on the surface of the Cux Mg1-x Fey Al2-y O4 particles. Cyclic voltammetry studies predicted the active lifetime of the oxygen carrier, which had not been reported until now. Cu0.75 Mg0.25 Fe1.5 Al0.5 O4 was expected to exhibit the greatest oxygen transfer capacity after 300 redox cycles and maintain an oxygen transfer efficiency of 92% until the 1000th redox cycle in the H2 -N2 /air redox system. This study concluded that the active metal species, containing Cu 2+ and Fe 3+ ions, were stably anchored in the spinel structure; this led to the reversible formation of oxygen vacancies in the spinel structure, resulting in an excellent oxygen transfer capacity that could be maintained for a long time.